Systematic Literature Review: Knowledge Management in Academic Leadership - Mulyana, Uus; Rofaida, Rofi; Sobandi, Ade; Siddiq, Andhika Mochamad (Journal of Business Management Education (JBME), 2024)
Leadership academics in education tall related with making Management policy source power, and development staff. Management knowledge focus on collection and dissemination information for increase learning and research. Systematic Literature Review (SLR) method with for journal Scopus indexed involves determine question research, planning search literature, collecting data from Scopus (2018-2023), evaluating and selecting relevant studies, as well analyze and synthesize data with the PRISMA model for identify gap research and create recommendation. Research result showing aspect critical in development education high, esp. in the era of digitalization and globalization. Leader role academic covers formation digital culture, promoting collaboration, and overcoming challenge ethics in management knowledge team. Effectiveness in management knowledge increase quality teaching and research, as well performance academic. Future research need focus on integration technology, adaptation in context multicultural, keeping balance mark academic with market demands, and promote continuity in education tall.